2006
DOI: 10.1002/cncr.21914
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cytological specimens from mediastinal lesions obtained by endoscopic ultrasound-guided fine-needle aspiration

Abstract: BACKGROUND Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) seems to be a powerful tool to obtain cytologic specimens from mediastinal and celiac lymph nodes, enlarged left adrenal glands, and intrapulmonary tumors with mediastinal extension. The diagnostic yield of EUS‐FNA and the accuracy of cytologic specimens was evaluated. METHODS Cytologic assessment of EUS‐FNA specimens was performed and specimens were classified as positive, negative, suspicious for malignancy, or unsatisfactory for diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…[7] Another study suggested a lymph node aspirate would be insufficient if one of the smears did not contain an area with numerous small lymphocytes or follicle center cells. [18] At the time of this study, we did not have well-defined criteria for sampling adequacy, but in general, we required lymphoid cells that were loosely associated or in aggregates. A consensus on adequacy criteria for these specimens will help improve the false-negative rates.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Another study suggested a lymph node aspirate would be insufficient if one of the smears did not contain an area with numerous small lymphocytes or follicle center cells. [18] At the time of this study, we did not have well-defined criteria for sampling adequacy, but in general, we required lymphoid cells that were loosely associated or in aggregates. A consensus on adequacy criteria for these specimens will help improve the false-negative rates.…”
Section: Discussionmentioning
confidence: 99%
“…They evaluated the procedure as superior in comparison with FNA, as surgical diagnostic procedures can be reduced, and the repetition of unsuccessful FNA is avoided. For the same reason, endoscopic ultrasound-guided FNA has become increasingly useful in obtaining cytologic specimens from mediastinal lesions [43, 44]. Larghi and colleagues [44] implemented an altered endoscopic ultrasound-guided FNA technique in a pilot study of 27 patients using continuous high, negative pressure suction for core tissue acquisition, and they compared this technique to standard endoscopic ultrasound-guided FNA.…”
Section: Diagnosis Of Thymomamentioning
confidence: 99%
“…Transesophageal and transbronchial ultrasound-guided aspirations are being used with a high degree of sensitivity and specificity. 6 However, in the present study all of the aspirations were percutaneous aspirations. Diagnostic yield in the present study (80.7%) is comparable to the study conducted by Shabb et al 8 Significantly, it is also comparable to the study by Sklair-Levy et al 14 on core biopsies.…”
Section: Discussionmentioning
confidence: 58%
“…Diagnostic accuracy ranges from 77% to 100% in various studies. [1][2][3][4][5][6] With the advent of computed tomography (CT) and endoscopic ultrasonography (US), FNAC has proved its role even in primary mediastinal lesions. 7,8 Addition of ancillary techniques such as immunocytochemistry, flow cytometry and electron microscopy helps increase diagnostic accuracy.…”
mentioning
confidence: 99%